Analisis kemampuan pemecahan masalah matematika materi sistem persamaan linier dua variabel ditinjau dari gaya belajar siswa kelas VIII SMP Negeri 1 Aikmel Tahun Ajarn 2024/2025 - Ardi, Arsista Ardi; Arjudin; Dwi Novitasari; Muhammad Turmuzi (FKIP Universitas Mataram, 2025)
This study aims to analyze mathematical problem-solving abilities on the topic of Systems of Linear Equations in Two Variables (SPLDV) from the perspective of learning styles among eighth-grade students at SMP Negeri 1 Aikmel in the 2024/2025 academic year. This study employs a descriptive qualitative approach. The subjects of the study consist of 6 students, selected using purposive sampling, comprising 2 students each with auditory, visual, and kinesthetic learning styles. Data collection instruments used in this study include learning style questionnaires, mathematical problem-solving tests, and interviews. Data were analyzed using descriptive qualitative analysis. The results of the study indicate that: 1) students with a visual learning style tend to solve problems presented in graphical form more quickly because they find it easier to understand concepts and ideas clearly when the problems are presented visually rather than in text; 2) students with an auditory learning style tend to experience difficulties and require more time to solve problems in graphical form because they are more accustomed to understanding information through listening rather than through visual representation; 3) students with kinesthetic and visual learning styles tend to have difficulty writing conclusions, as kinesthetic learners are more focused on the process of solving problems rather than formulating conclusions from the solutions obtained; 4) students with visual and auditory learning style are able to complete all four stages of Polya’s priblem-solving process, whereas students with kinestheticc learning style can only complete three out of four stages: understanding the problem, devising a plan, and carrying out the plan. Keywords: Mathematical Problem Solving, Learning Style, SPLDV